A decision model for selecting of areas for improvement in EFQM model - Dodangeh, Javad; Mohd Yusuff, Rosnah (IEEE, 2011)
To monitor the progress towards business excellence, thousands of organizations across the world use self-assessment on a regular basis. There are a few popular business excellence models that provide standard criteria against which an organization can measure its performances. European Foundation for Quality Management (EFQM) is the most popular ones. The EFQM Excellence Model was introduced at the beginning of 1992 as the framework for assessing organizations for the European Quality Award. It is now the most widely used organizational framework in Europe and across the world and it has become the basis for the majority of international, national and regional Quality Awards. It is a practical tool that can be used as a guide to identify areas for Improvement. However, the current EFQM model has some drawbacks and problems which are not able to identify the priorities in Area for Improvement (AFI). For organizations with limitations of time, budget and resources and cannot implement all the Area for Improvement, some standards or indexes and limitations should be defined for prioritizing and choosing the Area for Improvement. Using Topsis1 method which is one of the multi-attribute decision making model, the Area for Improvement can be identified. Therefore, this work will develop a method of evaluating, assessing and determining the Area for Improvement in the EFQM model. The results showed that the developed model is more valid and acceptable and the experts verified the model for selecting of Area for Improvement in EFQM in practice. The proposed model was employed in a case study and drawn out results from it and were evaluated from different points of view.